FORMATION OF DIGITAL AND RESEARCH COMPETENCES IN THE TRAINING OF IT PROFESSIONALS IN A MODERN UNIVERSITY - Sherman, Mykhaylo; Samchynska, Yaroslava; Sikelinda, Mariya; Yurzhenko, Alona (Journal of Information Technologies in Education (ITE), 2020)
The article is devoted to the formation of digital and research competences of future IT professionals by applying complex practice-oriented tasks on the example of the educational topic "Development of chatbots using free online designers". The study of this topic is recommended within such disciplines as "Office Computer Technologies", "Information Systems in the Social and Legal Sphere", "Computer Information Technologies" and corresponds to the educational programs of the first (bachelor's) educational level in "Software Engineering", "Computer Science" and "Information Systems and Technologies". The purpose of studying the chatbot development technologies is learning of modern information and communication technologies by students for their practical implementation in the development and maintenance of software, as well as ensuring the occupational activity of employees of different categories. The educational topic "Development of chatbots using free online designers", which is offered for teaching in a modern university, is aimed at generalizing theoretical knowledge and developing practical skills of students of Bachelor level majoring in design in free software environments. The use of chatbots is one of the effective modern ways of communicating with users on mobile devices, which allows companies to reduce costs and attract new customers as well as timely meet the needs of existing customers. The study of this topic by students resulted in development of a chatbot working in the Telegram platform, which consults and provides answers related to the company's activities. To create the bot the free BorisBot service was used. The experience of teaching the topic of chatbot development at Kherson State University showed that its application in the preparation of bachelors majoring in 121 "Software Engineering", 122 "Computer Science", 126 "Information Systems and Technologies" motivates students to solve profession-oriented tasks.